2000
DOI: 10.1897/1551-5028(2000)019<2725:peocac>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Calcium Against Chronic Waterborne Cadmium Exposure to Juvenile Rainbow Trout

Abstract: Juvenile rainbow trout (Oncorhynchus mykiss [Walbaum]) on 1% daily ration were exposed to 0 (control) or 2 g of cadmium as Cd(NO 3 ) 2 ·4H 2 O per liter added to four different calcium (Ca) concentrations: 260 (background), 470 (low), 770 (medium), or 1200 (high) M of Ca added as Ca(NO 3 ) 2 ·4H 2 O in synthetic soft water for 30 d. Mortality was highest (ϳ80%) in the background ϩ Cd treatment. Approximately 40% mortality was observed in the low ϩ Cd exposure; mortality was 10% or less for all other treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 38 publications
4
15
0
Order By: Relevance
“…This effect is commonly observed at Cd concentrations above 3 g L −1 (Giles, 1988;Reid and McDonald, 1988). For example, Hollis et al (2000) observed no effects in Oncorhynchus mykiss gills when these animals were exposed to 2 g L −1 of Cd for 30 days. In another study involving trout, the plasma levels of Ca 2+ did not decrease after chronic exposure to 3.6 g L −1 of Cd; this effect was only demonstrated in fish exposed to 6.4 g L −1 (Giles, 1988).…”
Section: Discussionmentioning
confidence: 97%
“…This effect is commonly observed at Cd concentrations above 3 g L −1 (Giles, 1988;Reid and McDonald, 1988). For example, Hollis et al (2000) observed no effects in Oncorhynchus mykiss gills when these animals were exposed to 2 g L −1 of Cd for 30 days. In another study involving trout, the plasma levels of Ca 2+ did not decrease after chronic exposure to 3.6 g L −1 of Cd; this effect was only demonstrated in fish exposed to 6.4 g L −1 (Giles, 1988).…”
Section: Discussionmentioning
confidence: 97%
“…It was also lower than the values of 1.61 and 3.12 nmol·g wet gill tissue -1 reported in RBT, acclimated to the same water chemistry as that used in the present study, by Hollis et al (1999) and Szebedinszky et al (2001), respectively. This discrepancy in the number of gill binding sites (B max ) among studies was probably due to the size or batch differences in fish and also differences in feeding regime (Hollis et al 2000b) and is certainly an issue that has to be given greater attention for further development of the present acute Cd BLM.…”
Section: Short-term (3-h) Gill CD and Ca Binding In Laboratoryreared mentioning
confidence: 99%
“…Toxicity of Cd is generally attributed to the free divalent cation Cd 2+ (Pagenkopf 1983). Waterborne Cd appears to enter mainly through chloride cells in the gills (Wicklund-Glynn et al 1994) and accumulates primarily in kidney, liver, and gills of fish (Hollis et al 1999(Hollis et al , 2000a(Hollis et al , 2000b. At acute waterborne concentrations, Cd severely disrupts Ca homeostasis, which ultimately leads to death (Verbost et al 1987; Reid and McDonald 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The speciation pattern of metals is influenced by the overall composition of the solution (synthetic or natural), in particular, properties like pH, hardness, ionic strength and the presence of complexing ligands such as inorganic ions, EDTA (in synthetic test media) and naturally occurring dissolved organic matter (DOM) expressed as dissolved organic carbon (DOC). The water chemistry and resulting speciation of the metal in the test media thus strongly influence the bioavailability and hence also the ecotoxicity of the metal (Bossuyt et al 2004;Bury et al 1999;Hollis et al 2000;Kramer et al 2004;Macdonald et al 2002;Richards et al 2001). The distribution of the metal among the various metal species, and the resulting concentrations of each of them can be predicted by chemical speciation models (Bhavsar et al 2004), but in spite of the recognised influence on the metal ecotoxicity, chemical speciation and physico-chemical characteristics of the aquatic system are rarely considered when reporting on ecotoxic effects for metals and deriving water quality criteria (Janssen et al 2000).…”
Section: Introductionmentioning
confidence: 99%